2016
DOI: 10.1063/1.4941968
|View full text |Cite
|
Sign up to set email alerts
|

Observation of second order ion acoustic Peregrine breather in multicomponent plasma with negative ions

Abstract: The experimental observation of second order ion acoustic Peregrine breathers in multicomponent plasma with negative ions is reported. A long wavelength initial perturbation on a continuous carrier frequency ∼0.5 ωpi (where ωpi is the ion plasma frequency) of finite amplitude is found to undergo self-modulation due to the interplay between nonlinear dispersive effect and group velocity dispersion because of modulational instability. Wave energy focusses to a smaller localized and isolated group of waves within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For instance, it has been well established that they may appear in physical systems as the consequence of the interplay between nonlinear and dispersive effects, under the activation of the so-called MI phenomenon [3][4][5][6][7][8]. Recently, interest in studying RWs has gone beyond oceanography and hydrodynamics [9,10] to reach some other areas related to optics and photonics [11][12][13][14], Bose-Einstein condensation [15][16][17], biophysics [18][19][20][21], plasma physics [22,23], just to name a few. Particularly, ion-acoustic super-RWs were found in an ultra-cold neutral plasma in the presence of ion-fluid and nonextensive electron distribution [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been well established that they may appear in physical systems as the consequence of the interplay between nonlinear and dispersive effects, under the activation of the so-called MI phenomenon [3][4][5][6][7][8]. Recently, interest in studying RWs has gone beyond oceanography and hydrodynamics [9,10] to reach some other areas related to optics and photonics [11][12][13][14], Bose-Einstein condensation [15][16][17], biophysics [18][19][20][21], plasma physics [22,23], just to name a few. Particularly, ion-acoustic super-RWs were found in an ultra-cold neutral plasma in the presence of ion-fluid and nonextensive electron distribution [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the same direction, magnetosonic RWs, of first and second order, were investigated numerically in a magnetized plasma [25]. The occurrence of fundamental and second-order RWs was also investigated in a relativistically degenerate plasma using the NLS equation [23]. Comparison between experimental and theoretical occurrences of RWs was proposed recently and applied to multicomponent plasmas with negative ions [26].…”
Section: Introductionmentioning
confidence: 99%
“…There are many non-linear space-time evolution equations that govern the dynamics and physics of these non-linear waves, for example, the family of the Korteweg-de Vries (KdV) equation and the non-linear Schrödinger equation (NLSE) etc. [22,23] It has been observed that a slow amplitude-modulated perturbation undergoes self-modulation and hence gives rise to localized pulses with huge amplitude. The ultimate consequence of the balance occurring between the non-linearities and the wave group dispersion is called an envelope soliton.…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory experiments have been carried out to generate rogue waves (RWs) in multicomponent plasma in the presence of negative ions. [22,23] It has been observed that a slow amplitude-modulated perturbation undergoes self-modulation and hence gives rise to localized pulses with huge amplitude. Moreover, it is noticed that the measured amplitude of the first-order RW is thrice the amplitude of the nearby carrier wave amplitude, which agrees with the rational solution of the NLSE.…”
Section: Introductionmentioning
confidence: 99%
“…32. A year ago, the so called critical plasma concentration was invoked for negative ions, in order to study the nonlinear evolution of ionacoustic envelope wavepackets and to establish the existence of second-order ion-acoustic "Peregrine solitons" (breathers) experimentally [33]. More recently, the different vibration modes occurring in negative-ion plasma in the presence of a streaming ion beam were investigated by means of one-dimensional electrostatic particle in cell (PIC) computer simulations [34].…”
Section: Introductionmentioning
confidence: 99%